POLA TATA HIJAU DI KOTA KENDARI - Sastrawati, Isfa (TERAS)
While the urban population grew rapidly, land need is increased as result in urban growth. This will be made the urban green open space more and more decrease. Existence of urban green open space has ecological, social, cultural, economic and esthetic functions. This research aims to know condition and problems of the urban green open space in Kendari city. The method analysis of this research is descriptive and explorative by using qualitative and quantitative approach. This study finding that not only size of urban green open space has been decreased, but also its quality. The spreading and access radius assessed less adequate, facility of urban green open space still less quantity, tree shading on parks and greenways less calm, and dense canopy still lushness. By the end of solution, concept development and management system of urban green open space is made to become input materials for stakeholders of Kendari city